Indirect Solar Drier for drying of Hill products - Aggarwal, R. K (Asian Journal of Agriculture and Rural Development, 2012)
An indirect solar drier of 25 kg capacity has been developed fitted with solar cell for running the fan. The bulbs are provided in the solar collector for air heating during clouds and evening & morning for faster drying reducing drying time. 15 such solar driers have been installed in the state. Various hill agricultural crops have been dried in solar drier by the farmers and collected. The market value of dried products has also been compared.